(untitled) (Eurasian Journal of Ecology, 2023)
In professional conditions, adaptation to unfavorable production factors is most often implemented through a resistance strategy that provides changes in the function of molecular and supramolecular systems. Unfavorable factors of the working environment can cause two differently directed reactions in a person - an increase in resistance (increase in resistance) and an increase in tolerance (tolerance, endurance). We conducted experimental studies of laboratory animals directly in the main workshops of the titanium-magnesium plant, where their body is exposed to a complex of toxic gases and dust (aerosol of titanium dioxide, dust of metallic titanium, titanium tetrachloride and its hydrolysis products, as well as chlorine and phosgene). In the experiment, the activity of the sympathetic-adrenal system was determined by the excretion of catecholamines - adrenaline, norepinephrine, dopamine and DOPA. We have revealed significant changes in the level of catecholamines in the organs of experimental animals. Adrenaline and norepinephrine in the liver tissue increased significantly in laboratory animals at 2; 4 and 12 weeks, kept in 1,2 and 3 shops compared with the control. The content of norepinephrine in the tissue of the adrenal glands, in the tissue of the heart in animals kept in the main workshops changed significantly compared to the control. These studies are of interest in the light of early detection of changes in the body when exposed to a complex of toxic gases and dust, the timely implementation of therapeutic, preventive measures prevents the development of occupational and somatic diseases.